Effects of Uremic Clearance Granules in Uremic Pruritus: A Meta-Analysis - Ping-Hsun Lu; Jen-Yu Wang; Hui-En Chuo; Po-Hsuan Lu (Toxins, 2021)
Uremic pruritus is common among patients with advanced or end-stage renal disease, with an incidence of >40% among patients on dialysis. Uremic clearance granules (UCGs) are effective in managing uremic pruritus and delay the progression of chronic kidney disease. We conducted a systematic review and a meta-analysis to evaluate the efficacy of UCG in patients with uremic pruritus. Several electronic databases were searched systematically from their inceptions until 19 July 2021. Randomized control trials evaluating the efficacy of UCG in patients with uremic pruritus were selected. Eleven trials including 894 participants were published between 2011 and 2021. Patients administered UCGs had a significantly decreased visual analog scale score (mean difference [MD], −2.02; 95% confidence interval [CI], −2.17 to −1.88), serum levels of hsCRP (MD, −2.07 mg/dL; 95% CI, −2.89 to −1.25; p < 0.00001), TNF-α (MD, −15.23 mg/L; 95% CI, −20.00 to −10.47; p < 0.00001]), β2-MG (MD, −10.18 mg/L; 95% CI, −15.43 to −4.93; p < 0.00001), and IL-6 (MD, −6.13 mg/L; 95% CI, −7.42 to −4.84; p < 0.00001). In addition, UCGs significantly reduced serum levels of creatinine, BUN, PTH, iPTH, phosphorus, and the overall effectiveness rate. UCGs could be an attractive complementary therapy for patients with uremic pruritus.